(untitled) (Research, Society and Development, 2022)
Knee ligament injuries have been widely discussed in recent years, driven by the high number of cases in sports practice. The aim of this study was to compare the muscle performance of athletes who participated in a rehabilitation program after reconstruction of the anterior cruciate ligament (ACL), using a software developed to assess parameters such as peak torque, total work and muscle power. Fifty-nine amateur athletes who underwent ACL reconstruction with a graft from the flexor muscle group, with 6 months of rehabilitation started immediately after surgery, were evaluated. The evaluation consisted of 5 concentric isokinetic contractions with a constant velocity of 60º/s for knee flexion and extension performed using an isokinetic dynamometer. The data obtained were analyzed using the Muscle Performance Analysis in Isokinetic Dynamometry® software, developed for this study. The results obtained allowed us to observe a difference of more than 10% between the sides for peak torque, total work and maximum power (p<0.05), with the extensor muscle group showing lower values for the operated side. The flexor muscle group did not present a significant difference in the same variables. The software developed in C /Matlab language allowed better visualization, interpretation and analysis of muscle performance, offering consistent results for all evaluated athletes. The results indicate that the 6 months of rehabilitation were not enough to promote symmetry of strength between the sides for the knee extensor muscle group, indicating a risk of returning to sport at this stage of treatment.